GOOD PERSONALITIES OF TEACHER NAINA MATHUR IN “HICHKI” FILM AND ITS RELEVANCE TO THE INDONESIAN TEACHER CHARACTER REVOLUTION - Sugeng Santoso; Setyo Ajie Wibowo; Yenny Warisa Sinaga (Journal of Innovative Technologies in Learning and Education, 2025)
This research analyzes the good personalities of Naina Mathur, a teacher in the Indian film "Hichki". The good personalities found will also be analyzed for their relevance to the character revolution needed by problematic teachers in Indonesia. The qualitative descriptive research method is used to present data in the form of sentences (non-numeracy). Data collection is assisted by observation and note-taking technique. Data processing is carried out using the Miles and Huberman model. The results of this research indicate that Teacher Naina Mathur has good characteristics, including: honest, discipline, rational, fair, authoritative, patient, open-minded, humorous, sympathy, humble, creative, friendly, and love to learn. These good personalities are relevant as sources in the teacher character revolution.